THE INFLUENCE OF LEARNING ACHIEVEMENT, SOCIOECONOMIC STATUS OF PARENTS, AND LEARNING MOTIVATION ON THE INTEREST IN CONTINUING EDUCATION TO HIGHER EDUCATION IN CLASS XII STUDENTS COMPETENCE OF ACCOUNTING AND FINANCIAL EXPERTISE OF SMKN 13 JAKARTA: THE INFLUENCE OF LEARNING ACHIEVEMENT, SOCIOECONOMIC STATUS OF PARENTS, AND LEARNING MOTIVATION ON THE INTEREST IN CONTINUING EDUCATION TO HIGHER EDUCATION IN CLASS XII STUDENTS COMPETENCE OF ACCOUNTING AND FINANCIAL EXPERTISE OF SMKN 13 JAKARTA - Wawan Aprianto; Sri Zulaihati; Ati Sumiati (Yayasan Education and Social Center, 2022)
This study aims to determine whether there is an effect of learning achievement, parents' socioeconomic status and learning motivation on students' interest in continuing their education to higher education in class XII students of financial and institutional accounting expertise competence at SMKN 13 Jakarta in the 2021/2022 academic year either simultaneously or partially. The population of class XII students of financial and institutional accounting expertise competency is 108 students, with the T-Yamane formula obtained a sample of 85 students and using Proportional Random Sampling. The data collection technique for the study achievement variable (X1) uses secondary data in the form of report cards for the fifth semester. The socio-economic status variable of parents (X2) uses secondary data, namely parents' income data. Furthermore, for the variable of learning motivation (X3) and interest in continuing education to higher education (Y) using primary data in the form of a questionnaire with Validity Test and Reliability Test. Analysis of the data used is descriptive analysis of percentages and multiple linear regression. The results of the study showed that there was an effect of learning motivation (62.6%), and there was no effect of learning achievement, and the socioeconomic status of parents on students' interest in continuing their education to class XII tertiary institutions of financial accounting and institutional competence at SMKN 13 Jakarta in the 2021/2022 academic year. Meanwhile, simultaneously all independent variables have an effect (63%)